Ulayat’s Fate: Tradition, Development and Conflict in West Sumatra’s Oil Palm Plantations - Edi Indrizal; Ermayanti; Ade Irwandi (Universitas Andalas, 2026)
This paper describes the fate of customary land surrendered by indigenous peoples as part of the government's development programme to increase the palm oil plantation industry to support the economy and modernisation. The approach used is ethnography with a case study focus. Data were collected through interviews and observation techniques as well as literature study. informants were selected by grouping the interests of individuals and tribal groups (Ninik Mamak, Tanjung Tribe, KAN, Companies, Local Government, and Community Leaders). As a result, after the Nagari Bawan and Manggopoh communities surrendered their land to PT AMP Plantation with a mechanism that was considered in accordance with customary rules and applicable laws and regulations, it eventually led to conflict. The Ninik Mamak of Nagari Bawan was provoked into an internal conflict over who had the most authority in the land, and some Ninik Mamak used customary rules for political interests. Likewise, the community of Nagari Manggopoh, namely the Tanjung tribe, has ventured into conflict with plasma land management and maintaining the status quo as a full landowner. In addition, the Tanjung tribe experienced conflicts between fellow Ninik Mamak, who claimed that they had the most power over the control of plasma products and were entitled to personal benefits. They (the Tanjung tribe) are also in conflict with community groups, Ninik Mamak (KAN), and the company because of the lack of transparency in the provision of plasma distribution.